Paclitaxel/carboplatin with or without sorafenib in the first‐line treatment of patients with stage III/IV epithelial ovarian cancer: a randomized phase II study of the Sarah Cannon Research Institute. (31st December 2014) - Hainsworth, John D.; Thompson, Dana S.; Bismayer, John A.; Gian, Victor G.; Merritt, William M.; Whorf, Robert C.; Finney, Lindsey H.; Dudley, B. Stephens
Abstract This trial compared the efficacy and toxicity of standard first‐line treatment with paclitaxel/carboplatin versus paclitaxel/carboplatin plus sorafenib in patients with advanced ovarian carcinoma. Patients with stage 3 or 4 epithelial ovarian cancer with residual measurable disease or elevated CA‐125 levels after maximal surgical cytoreduction were randomized (1:1) to receive treatment with paclitaxel (175 mg/m2, 3 h infusion, day 1) and carboplatin (AUC 6.0, IV, day 1) with or without sorafenib 400 mg orally twice daily (PO BID). Patients were reevaluated for response after completing 6 weeks of treatment (two cycles); responding or stable patients received six cycles of paclitaxel/carboplatin. Patients receiving the sorafenib‐containing regimen continued sorafenib (400 PO BID) for a total of 52 weeks. Eighty‐five patients were randomized and received treatment.Efficacy was similar for patients receiving paclitaxel/carboplatin/sorafenib versus paclitaxel/carboplatin: overall response rates 69% versus 74%; median progression‐free survival 15.4 versus 16.3 months; 2 year survival 76% versus 81%. The addition of sorafenib added substantially to the toxicity of the regimen; rash, hand–foot syndrome, mucositis, and hypertension were significantly more common in patients treated with sorafenib. The addition of sorafenib to standard paclitaxel/carboplatin did not improve efficacy and substantially increased toxicity in the first‐line treatment of advanced epithelial ovarian cancer. Based on evidence from this study and other completed trials, sorafenib is unlikely to have a role in the treatment of ovarian cancer.